A new genus and species of Polynoidae (Annelida, Polychaeta) from Pine Island Bay, Amundsen Sea, Southern Ocean—a region of high taxonomic novelty - Neal, L.; Barnich, R.; Wiklund, H.; Glover, A.g. (Zootaxa, 2012)
We describe a new genus and species of polychaete worm (Polynoidae, Macellicephalinae) from a previously unsampled areaof the Southern Ocean, Pine Island Bay in the Amundsen Sea. Austropolaria n. gen. is differentiated from other genera in thesubfamily Macellicephalinae by a combination of morphological characters such as the number of pharyngeal papillae, bodysegments, elytra, and position of ventral cirrus. The type species of this genus, Austropolaria magnicirrata n. sp., is described based on morphological characters, supplemented by molecular data.